Account Management and Accounting Operations Specific to the Agricultural Cooperatives (VIII) - Paul C. ȘCHIOPU (CECCAR Business Review, 2022)

(untitled)
Considering that, as regards the fast-growing agricultural cooperative sector (currently, approximately 4,000 agricultural cooperatives are registered), there are neither operating rules, nor works guiding the co-operators in the economic activity, we consider that the article hereby may be extremely useful both for them and the professional accountants working in the field. From the point of view of setting up, organization and functioning, agricultural cooperatives have certain particularities that differentiate them from the other entities in the market economy, this also being the reason why we deemed it necessary to deal with the organisation and management of registers, as well as of some accounting operations, grouping them into specific operations and joint operations of all types of agricultural cooperatives.